Determination of sex by measurement of area of mastoid triangle in human skull (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Identification is one of the parameter that is unique to an individual and is required frequently in medico-legal scenario. Since bones resist putrefaction for considerable long time therefore they provide abundance of information for the purpose of identification of an individual. Skull is one such bone which provides one of the best parameters to ascertain sex with reasonable accuracy. A prospective randomized study has been conducted in the Department Of Forensic Medicine, University College of Medical Sciences & Guru Teg Bahadur Hospital, Delhi. In this study area of mastoid triangle is correlated with the sex of the individual in 200 cases (100 male and 100 female). The dead bodies of age group between 18 years to 60 years were selected for the study
Keywords: parameter; prospective randomized